Risk Sharing and Network Formation. - Fafchamps, M; Gubert, F (GPRG, 2006)
In this paper we examine whether risk sharing networks are formed so as to maximize the mutual gains from pooling income risk. The bene…t from risk pooling is largest when households have different income pro…les - e.g., different occupations - and are subjected to di¤erent sources of risk - e.g., live far apart. Gains from risk sharing therefore increase with social and geographical distance. But distance also raises the cost of interpersonal links. The net e¤ect on link formation is a priori indeterminate. We investigate this issue empirically using survey data from the rural Philippines.